(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم الاقتصادية والقانونية, 2013)
إن وضع الدول العربية المنضمة إلى منطقة التجارة الحرة العربية الكبرى بعد مرور عدة سنوات للتحرير الكامل للرسوم والقيود الجمركية فيما بينهم, يتطلب ايلاء أهمية كبرى لقياس درجة الفاعلية التجارية البينية فيما بين هذه الدول, لمعرفة الوضع الحقيقي لطبيعة وفعالية التجارة البينية فيما بينهم, خاصة وأن الأرقام المتوفرة حول هذا الأمر غالباً ما تؤدي إلى نتائج مضللة. بناءً على ما تقدم جاء بحثنا هذا لدراسة التبادل التجاري بين سورية ودول مجلس التعاون الخليجي العربي باعتبار هذه الدول الأهم في إطار منطقة التجارة الحرة العربية الكبرى, وقياس درجة الفعالية التجارية البينية فيما بينهم, بما يعكس مدى الشمولية في العلاقات التجارية وانتشارها بين هذه الدول, وتجاوز ما تفرزه الأرقام المضللة عن طبيعة التجارة البينية فيما بينهم. The current situation of the Arab countries acceding to the Great Arab Free Trade Area after several years to complete liberalization of fees and customs restrictions between them, requires paying great attention to measuring the effectiveness of commercial interfaces between these states and to know the real situation of the nature and effectiveness of intra-trade among themselves, especially since the figures available about this often lead to misleading results. Based on the above-mentioned discussion comes the necessity this study of trade exchange between Syria and the Gulf Cooperation Council (GCC) Arab, as these countries are the most important in the context of the Great Arab Free Trade Area. This study also focuses on measuring the effectiveness of commercial interfaces between them, reflecting the extent of inclusiveness in trade relations and their spread between these countries, exceeding the misleading figures about the nature of intra-trade among these countries.